Small pulmonary vascular alteration and acute exacerbations of COPD: quantitative computed tomography analysis - Wang, Zhiyue (Int J Chron Obstruct Pulmon Dis, 2016)
The morphologic alterations of pulmonary small vessels measured by computed tomography (CT) have been used to evaluate chronic obstructive pulmonary disease (COPD). However, the relationship between small pulmonary vascular alteration and acute exacerbations of COPD (AECOPD) is not well understood. The aim of this study was to evaluate the cross-sectional area (CSA) of small pulmonary vessel alterations measured on CT images and investigate its relationship with the COPD severity staged by the degree of airflow limitation and the occurrence of AECOPD. We retrospectively reviewed CT scans, clinical characteristics, and pulmonary function test results of 153 patients with COPD. All the patients were divided into AECOPD and non-AECOPD group according to the COPD staging and pulmonary function test results. The percentages of the total CSA less than 5 mm(2) and equal to 5–10 mm(2) over the lung area (%CSA(<5) and %CSA(5–10), respectively) were measured. The %CSA(<5) steadily decreased in relation to the increase of COPD severity. In addition, %CSA(<5) of the AECOPD group was significantly lower than that of the non-AECOPD group (0.41±0.13 versus 0.68±0.18, P<0.001), and the optimal cutoff value was 0.56 (sensitivity, 0.863; specificity, 0.731). Therefore, small pulmonary vascular alteration, as measured by %CSA(<5), could indicate not only the degree of COPD severity, but also the occurrence of AECOPD.